THE TOOLS AND MONTE CARLO WORKING GROUP Summary Report from the Les Houches 2009 Workshop on TeV Colliders - Butterworth, J; Maltoni, F; Moortgat, F; Richardson, P; Schumann, S; Skands, P; Alwall, J; Arbey, A; Basso, L; Belov, S; Bharucha, A; Braam, F; et al. (2010)
This is the summary and introduction to the proceedings contributions for the Les Houches 2009 "Tools and Monte Carlo" working group.